The concept of the body in Chinese and European philosophical traditions: comparative analysis - Bouiko, Tatsiana N.; Wu, Xiaoyan (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The concept of the body in Chinese and European philosophical traditions is studied. The differences of views on this concept are presented. It is determined that in Chinese philosophy, both traditional and modern, the body is comprehended not only from the biological, but also from the socio-cultural point of view, as the originally spiritualised body contains the history of a particular society. It is revealed that in European philosophy the body is understood as a physical object. It is noted that the body-oriented approach developed on the basis of non-classical European philosophy is becoming more and more widespread in social and humanitarian sciences. It is established that the actualisation of the problems of human corporeality in Chinese philosophy is connected with the influence of European science and culture.
Keywords: body; corporeality; body-oriented approach; rationalism; phenomenology; postmodernism